دور خفة الحركة الاستراتيجية في مربع التسويق الذهبي دراسة ميدانية لعينة من الجامعات الاهلية في محافظة السليمانية - رشيد, نيان كمال; خورشيد, ساره صباح (Sulaimani Journal for Humanities, 2022)
Title: The role of Strategic Agility in Golden Marketing Square (An empirical study in a sample of private universities in Al-Sulaimainiya governorate). - Study problem: 1. What is the nature of the relationship between strategic agility and golden marketing square? 2. Does the studied sample have enough understanding about strategic agility? 3. Does the studied sample have a clear vision of golden marketing square? - The study sample and society: A number of private universities in Sulaimani governorate have been involved, namely (The American University, Ishik University, The Human Development University, Cihan University, Komar University). The respondents to the study consists of deans, department heads, lecturers in the three later universities mentioned above in which their numbers reached (86). - Methodology and tools of the study: A descriptive and analytical methodology has been adopted in this study, and questionnaire is used as a tool for collecting data. - Conclusions: 1. Strategic agility has role in achieving golden marketing square (IPSL).